Adsorption of arsenic using chitosan magnetic graphene oxide nanocomposite - Sherlala, A.I.A.; Abdul Raman, Abdul Aziz; Bello, Mustapha Mohammed; Buthiyappan, Archina (Elsevier, 2019)
Chitosan-magnetic-graphene oxide (CMGO) nanocomposite was prepared for arsenic adsorption. The nanocomposite was characterized through BET, FTIR, FESEM, EDX, and VSM analyses. These characterizations confirmed the formation of CMGO nanocomposites with high specific surface area (152.38 m2/g) and excellent saturation magnetization (49.30 emu/g). Batch adsorption experiments were conducted to evaluate the performance of the nanocomposite in the adsorption of arsenic from aqueous solution. The effects of operational parameters, adsorption kinetic, equilibrium isotherm and thermodynamics were evaluated. The removal efficiency of arsenic increased with increasing adsorbent dosage and contact time. However, the effect of pH followed a different pattern, with the removal efficiency increasing from acidic to neutral pH, and then decreasing at alkaline conditions. The highest adsorption capacity (45 mg/g) and removal efficiency (61%) were obtained at pH 7.3. The adsorption kinetic followed a pseudo-second-order kinetic model. The analysis of adsorption isotherm shows that the adsorption data fitted well to Langmuir isotherm model, indicating a homogeneous process. Thermodynamic analysis shows that the adsorption of As(III) is exothermic and spontaneous. The superparamagnetic properties of the nanocomposite enabled the separation and recovery of the nanoparticles using an external magnetic field. Thus, the developed nanocomposite has a potential for arsenic remediation. © 2019 Elsevier Ltd